Synthesis of novel 6-substituted-3(2H)-pyridazinone-2-acetyl-2-(substituted/-nonsubstituted benzal)hydrazone derivatives and acetylcholinesterase and butyrylcholinesterase inhibitory activities in vitro - Utku, Semra; Gökçe, Mehtap; Orhan, İlkay; Şahin, M Fethi (Arzneimittelforschung, 2011)
In this study thirteen 6-substituted-3(2H)-pyridazinone-2-acetyl-2-(substituted/-nonsubstituted benzal)hydrazone V derivatives were synthesized as acetylcholinesterase and butyrylcholinesterase inhibitors. Ten of the synthesized compounds were synthesized for the first time in this study and the rest of them had been synthesized in a previous study. The structures of compounds V were elucidated by IR, 1H-NMR and MASS spectra. The acetylcholinesterase (AChE) and butyrylcholinesterase (BChe) inhibitory activities of V derivatives were measured using Ellman's method. While some of the 6-substituted-3(2H)-pyridazinone-2-propyl-3-(substituted/-nonsubstituted benzal)hydrazone V derivatives exhibited significant AChE inhibitory activity, none of the compounds showed BChE inhibitory activity. These results indicate that V derivatives were AChE inhibitors with AChE/BChE selectivity.
Keywords: Acetylcholinesterase inhibitors; Benzal hydrazone; Butyrylcholinesterase inhibitors; 3(2H)-Pyridazinone